Charger Structure with Transistor Based Isolator for Parallel Charging of Series Connected Battery Cells - Goksu, Omer Faruk; Vural, Revna Acar (IEEE, 2019)
A new generation of highly efficient batteries is being developed to be used as a power source for electronic devices. Basic battery management systems do not charge the battery cells and require external chargers. For a flexible charging system, the built-in chargers are located into each battery management module. Thus, charging systems can be independent of the number of battery cells. For the health of the battery cell, battery charging methods are as important as usage limits. The aim of the proposed study is to eliminate the energy consuming excess energy and to apply the newly developed and more efficient charging algorithms to the designed structure. For this purpose, a new circuit structure has been developed instead of relay elements which activate the charging line in order to charge the battery cells in parallel. As a result of this study, proposed structure provided faster charging and higher energy efficiency.
Keywords: Engineering